Sistem Informasi Geografis berbasis Web untuk Penentuan Prioritas Pembangunan Embung - Kornelius Satria Budiyanto; Ike Pertiwi Windasari; Yudi Eko Windarto; Desyta Ulfiana (Politeknik Caltex Riau, 2020)
Spring water is a human need for daily life. One of the benefits is to irrigate agricultural land. Agricultural land in Semarang Regency dried up every dry season in the last few years. Semarang Regency local government had identified 8 areas as the candidate of small dam construction locations for short term priority. The selection of small dam locations becomes a special issue in data processing in the Water Resources Sector which has many criteria to be aware of. The obtained data can be stored in database of GIS. Therefore, decision support system is needed to determine the best small dams priority. The method used in this system is the TOPSIS. Data that has been processed will be implemented to determine the best small dams priority in a region and displayed visually using Carto Map. System are built using the Codeigniter framework based PHP and MySQL database. In its implementation, the Rapid Application Development (RAD) method is used. Based on the calculation results obtained the first three sequences that have the largest live storage and the lowest water cost that can be prioritized are Mluweh, Lebak, and Pakis.